Gastric cancer prewarning and early diagnosis system - Cui, Daxiang (Springer, 2017)
The book explores recent developments in the application of nanotechnology in the early detection of gastric cancer. It discusses various aspects, such as screening for gastric cancer-associated biomarkers; establishing new ultrasensitive detection methods based on nanoparticle labeling and nanoeffects; developing a new generation of nanodevices for high-throughput examination of serum and breath biomarkers; developing multifunctional nanoprobes for targeted imaging and simultaneous therapy of gastric cancer; evaluating the biosafety of multifunctional nanoprobes; and the establishment of a pre-warning and early diagnosis system. It also presents clinical applications and prospects. The book provides a valuable reference for researchers in nanomedicine and clinicians involved in gastric cancer and radiology.
Keywords: Stomach -- Cancer.; Stomach -- Cancer -- Diagnosis.; Nanobiotechnology.; elektronické knihy; electronic books